Costos y precios en las empresas estatales de servicios públicos en Colombia: la economía política, el modelo legal y algunas tasas redistributivas en el servicio de aseo - Rubiano Páez, Nestor (Universidad del Rosario, 2017)
The principal aim of this work is to comparea ideal model with the reality. It is an analysis of both, positive and normative economics in the market of home public services in Colombia. The first chapter focus on the most possible  and  realistic behaviour of economicagents in the public en1te ¡¡l,t se: political groups,  managers,  workersand consumers. A set ofassun pt:ion:s. makes up a political economy model, which allows  ·to draw out condusions  about enterprises financial dynamics.